2016
DOI: 10.1186/s40798-016-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Whole Blood Donations on Aerobic Capacity and Hemoglobin Mass in Moderately Trained Male Subjects: A Randomized Controlled Trial

Abstract: BackgroundThe aims of the present study were to investigate the impact of three whole blood donations on endurance capacity and hematological parameters and to determine the duration to fully recover initial endurance capacity and hematological parameters after each donation.MethodsTwenty-four moderately trained subjects were randomly divided in a donation (n = 16) and a placebo (n = 8) group. Each of the three donations was interspersed by 3 months, and the recovery of endurance capacity and hematological par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…All 8 studies included were experimental in nature, incorporating a before and after blood donation approach, with only the Meurrens, et al [20] study using a control (sham bleed) group. Participant numbers ranged from 9–24 (13.5 ± 4.9) and hence appeared low, unfortunately only two studies, that of Judd, et al [31] and Meurrens, et al [20] provided power calculations to reflect sample size, although justification for sample size was presented in all studies except Krip, et al [32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 8 studies included were experimental in nature, incorporating a before and after blood donation approach, with only the Meurrens, et al [20] study using a control (sham bleed) group. Participant numbers ranged from 9–24 (13.5 ± 4.9) and hence appeared low, unfortunately only two studies, that of Judd, et al [31] and Meurrens, et al [20] provided power calculations to reflect sample size, although justification for sample size was presented in all studies except Krip, et al [32].…”
Section: Resultsmentioning
confidence: 99%
“…Research papers have historically determined that BD decreases [15,16,19,20] However, in this analysis the confidence intervals have not produced statistical significance. Individual studies have too much variance and therefore the pooled data using the Cohen’s d allows for comparisons across all papers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study indicated that haematological parameters are cumulatively affected upon repeated donations. Furthermore, the positive training effect observed in the placebo group was absent in the donation group , the latter exemplifying the benefit of a placebo group. A Cochrane review found 30 randomized trials of iron supplementation in blood donors and concluded that iron supplementation effectively increased haemoglobin levels and iron stores and reduced donor deferral for low haemoglobin levels.…”
Section: What Can We Do?mentioning
confidence: 87%